Quantitative analysis of urban sprawl in Tripoli using Pearson's chi-square statistics and urban expansion intensity index - Al-sharif, Abubakr A. A.; Pradhan, Biswajeet; Mohd Shafri, Helmi Zulhaidi; Mansor, Shattri (IOP Publishing, 2014)
Urban expansion is a spatial phenomenon that reflects the increased level of importance of metropolises. The remotely sensed data and GIS have been widely used to study and analyze the process of urban expansions and their patterns. The capital of Libya (Tripoli) was selected to perform this study and to examine its urban growth patterns. Four satellite imageries of the study area in different dates (1984, 1996, 2002 and 2010) were used to conduct this research. The main goal of this work is identification and analyzes the urban sprawl of Tripoli metropolitan area. Urban expansion intensity index (UEII) and degree of freedom test were used to analyze and assess urban expansions in the area of study. The results show that Tripoli has sprawled urban expansion patterns; high urban expansion intensity index; and its urban development had high degree of freedom according to its urban expansion history during the time period (1984-2010). However, the novel proposed hypothesis used for zones division resulted in very good insight understanding of urban expansion direction and the effect of the distance from central business of district (CBD).